Vantage point : the sixth estate and other discoveries - Teodoro, Luis V., 1941- (Quezon City : UP Press, 2014)
Collection of essays on the Philippine political, social and economic condition.
In English.
Keywords: Philippines -- Politics and government -- 21st century; Philippines -- Social conditions -- 21st century; Philippines -- Economic conditions -- 21st century